2012
DOI: 10.4049/jimmunol.1003804
|View full text |Cite
|
Sign up to set email alerts
|

Lamin B Receptor Regulates the Growth and Maturation of Myeloid Progenitors via its Sterol Reductase Domain: Implications for Cholesterol Biosynthesis in Regulating Myelopoiesis

Abstract: Lamin B receptor (LBR) is a bifunctional nuclear membrane protein with N-terminal lamin B and chromatin binding domains plus a C-terminal sterol Δ14 reductase domain. LBR expression increases during neutrophil differentiation and deficient expression disrupts neutrophil nuclear lobulation characteristic of Pelger-Huët anomaly. Thus LBR plays a critical role in regulating myeloid differentiation, but how the two functional domains of LBR support this role is currently unclear. We previously identified abnormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 74 publications
(108 reference statements)
1
45
0
Order By: Relevance
“…Further studies demonstrated that increases in Lbr expression during neutrophil differentiation of these EML/EPRO-like cells coincided with increased expression of both C/EBPε and C/EBPε-regulated neutrophil genes, including those encoding murine neutrophil collagenase and neutrophil gelatinase (20). We therefore investigated whether C/EBPε is required for Lbr transcription.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Further studies demonstrated that increases in Lbr expression during neutrophil differentiation of these EML/EPRO-like cells coincided with increased expression of both C/EBPε and C/EBPε-regulated neutrophil genes, including those encoding murine neutrophil collagenase and neutrophil gelatinase (20). We therefore investigated whether C/EBPε is required for Lbr transcription.…”
Section: Resultsmentioning
confidence: 98%
“…To determine in vivo if either GABPα or PU.1 occupies either Ets binding site, or if C/EBPε interacts with the proximal C/EBP binding site, ChIP was performed using extracts from the original EML and EPRO cells, which exhibit varying levels of Lbr (20) and each transcription factor during neutrophil differentiation (Fig. 2A, 2B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations